2012
DOI: 10.1080/02703149.2012.684541
|View full text |Cite
|
Sign up to set email alerts
|

“Can't Have it All”: Representations of Older Women in Popular Culture

Abstract: Representations of older women in the media are defined by the double marginalization of age and gender. The analysis presented here illustrates four major stages in the development of such images: invisibility of older women, stereotypization, ghettoization, and integration. All of these forms continue to circulate simultaneously in popular media at the current time. The feminist critique of these representations suggests that they might be playing a significant role in how women interpret and experience agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 33 publications
(28 reference statements)
0
22
0
1
Order By: Relevance
“…In 2014 her critics said that she is too old to run again for the presidency, although those same critics had no concerns about Ronald Reagan's or John McCain's age when they ran for president (Tomasky, ). The more negative portrayal of older women than older men in popular culture (including the greater number of jokes about old women; Crawford & Unger, ; Lemish & Muhlbauer, ) and the greater pressure on women than on men to hide signs of aging (Dingman, Otte, & Foster, ; e.g., hair dye, “antiaging” skin cream, botox) may result in older women being ashamed of their age (Holstein, ) and more sensitive to age‐related microaggressions (i.e., brief, sometimes ambiguous actions that communicate a derogatory view of a particular social group and make the individual targets of the action feel inferior; Heintz, DeMucha, Deguzman, & Softa, ).…”
Section: Ageism and The Double Standard Of Agingmentioning
confidence: 99%
“…In 2014 her critics said that she is too old to run again for the presidency, although those same critics had no concerns about Ronald Reagan's or John McCain's age when they ran for president (Tomasky, ). The more negative portrayal of older women than older men in popular culture (including the greater number of jokes about old women; Crawford & Unger, ; Lemish & Muhlbauer, ) and the greater pressure on women than on men to hide signs of aging (Dingman, Otte, & Foster, ; e.g., hair dye, “antiaging” skin cream, botox) may result in older women being ashamed of their age (Holstein, ) and more sensitive to age‐related microaggressions (i.e., brief, sometimes ambiguous actions that communicate a derogatory view of a particular social group and make the individual targets of the action feel inferior; Heintz, DeMucha, Deguzman, & Softa, ).…”
Section: Ageism and The Double Standard Of Agingmentioning
confidence: 99%
“…Previous research on the representation of older people in the media supports our finding that older women were less likely to be present than older men [ 18 – 20 , 29 ]. Our finding that younger men were more likely to be depicted in news stories in newspapers and older women more likely to be depicted in non-news items could be seen as a double discrimination of age and gender and points again to older women having very low status within the media, if one accepts the argument that the news underrepresents people of lower status and that this is a gendered imbalance (see also [ 42 , 66 ]). This finding could also be interpreted in the light of news value theory, in which it is argued that certain factors are associated with events that become news [ 67 ].…”
Section: Discussionmentioning
confidence: 88%
“…As indicated above, research has shown that older women are particularly underrepresented across a range of media. Feminist critique of media representations suggests that underrepresentation may play a significant role in how women interpret and experience ageing [ 42 ]. In addition, in both developing and developed countries, women are generally shown in traditionally feminine and stereotyped roles, and they are often portrayed in a negative and circumscribed manner [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Placed in the far right-hand corner, rather than being placed somewhere in the middle of the group, is another indication of her subordinate role. However, from a different perspective, she is not in her private space, nor in a vulnerable or helpless situation, which is quite the contrary to more usual media representations of elderly people (Lemish and Muhlbauer, 2012). In this sense, she is challenging the conventional construction of elderly people: she is outside, independent and an active supporter of women's rights.…”
Section: / 18mentioning
confidence: 92%